1984
DOI: 10.1038/308850a0
|View full text |Cite
|
Sign up to set email alerts
|

Common non-hormone binding component in non-transformed chick oviduct receptors of four steroid hormones

Abstract: Steroid hormones produce a response in target cells by binding to hormone-specific soluble receptors, which undergo a transformational change, leading to their interaction with chromatin and to modified gene expression. In a previous paper, we described a monoclonal antibody, BF4, that specifically recognizes and binds the non-transformed '8S' form of chicken oviduct progesterone receptor (8S-PR). We now show that BF4 does not form an immune complex with the 4S transformed form of 3H-progestin-labelled progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
2
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 437 publications
(152 citation statements)
references
References 16 publications
6
141
2
3
Order By: Relevance
“…The function of this 90-kDa antigen is not yet understood. Moreover, recent studies have shown that the molybdate-stabilized 8-S forms of the estrogen and androgen receptors from chick oviduct cytosol, as well, interact with BF4 monoclonal antibody [16]. However, when gradient ultracentrifugation was performed in the presence of 0.5 M KCl, all steroid hormone receptors sedimented at z 4 S, irrespective of the presence of BF4 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 95%
“…The function of this 90-kDa antigen is not yet understood. Moreover, recent studies have shown that the molybdate-stabilized 8-S forms of the estrogen and androgen receptors from chick oviduct cytosol, as well, interact with BF4 monoclonal antibody [16]. However, when gradient ultracentrifugation was performed in the presence of 0.5 M KCl, all steroid hormone receptors sedimented at z 4 S, irrespective of the presence of BF4 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 95%
“…It is one of the most abundant cellular proteins found even under nonstress conditions. It has been found to be associated with a number of other intracellular proteins, including actin [28,29], pp60"-"', pp140fp", ~~94~"" [30,31], and steroid hormone receptors [32]. It is suggested that HSP90 plays several important roles in cells, one being to act as a chaperon.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Hsp90 was found to be associated with several different clients such as protein kinases and nuclear steroid receptors (e.g. glucocorticoid receptor) (Joab et al, 1984;Schuh et al, 1985;Smith, 1993;Smith et al, 1992). Since then, Hsp90 clients have grown tremendously owing to genome-wide high throughput studies.…”
Section: Ii41122 the Hsp90 Chaperone Systemmentioning
confidence: 99%